Vitamin D levels in nasopharyngeal carcinoma of the Minangkabau ethnic group - Rahman, Sukri; Ali, Hirowati; Indra, Beni (Oto Rhino Laryngologica Indonesiana, 2023)
Background: The etiology of nasopharyngeal carcinoma (NPC) is not yet known with certainty, but is suspected to be an interaction of multiple factors. Nasopharyngeal carcinoma is closely related to Epstein-Barr virus (EBV) infection which interacts with genetic susceptibility and environmental factors. Various studies have reported the relationship of vitamin D with the risk of various cancers, but very little research has a relationship with NPC. Objective: This study was conducted to analyze the association of vitamin D levels with nasopharyngeal carcinoma in the Minangkabau ethnic group. Methods: This study was a cross-sectional study comparing plasma levels of vitamin D (25(OH)D) in new patients with NPC of the Minangkabau ethnic who were treated at Dr. M. Djamil Padang with healthy control plasma. Result: This study found that the average vitamin D level in the NPC group was higher than the control group. Vitamin D levels in this study varied in both cases and controls. In the NPC group, vitamin D levels varied from 14.64 to 75.56 ng/ml. Most of the NPC group had normal vitamin D levels (69.6%), and in controls, vitamin D levels also varied from 6.06 to 73. .96 ng/ml, and most of them were also with normal levels (52.2%). There was no statistically significant difference between cases and controls (p>0.05). Conclusion: This study found no association between the level of vitamin D and the incidence of nasopharyngeal carcinoma in the Minangkabau ethnic group.